The intelligibility of Malaysian English to International Chinese undergraduates / Chin Jing Yi - Chin, Jing Yi (2014)
A recurrent debate invoked with the precipitate growth of English as an International Language (EIL), is seldom separable from the issue of intelligibility particularly on the subject of how readily intelligible are non-native English varieties in an international context. With more and more learners of English studying in Outer Circle and Expanding Circle countries, it is necessary to find out if there are any intelligibility problems that these non-native speakers of English could have faced while residing in the aforementioned countries such as in Malaysia and Singapore. This is also the case for students from China who are studying in Malaysia, a multiracial country where the English spoken is nativised by the diverse local languages. Hence, this research aims to investigate to what extent Malaysian English is intelligible to international students with considerations on the English spoken by the different ethnic groups in Malaysia. Using Jenkins’ LFC (1998, 2000, 2002) and Seidlhofer’s lexicogrammatical ‘sins’ (2001a, 2001b) as the primary frameworks, this research examines the features of Malaysian English discovered in the speech of six Malaysian students and its intelligibility to 20 students from China. The results shown are generally in accord with Jenkins’ LFC and Seidlhofer’s lexicogrammatical ‘sins’. This is an indication that intelligibility of non-native Englishes could be retained in communications between non-native speakers of English. There are also additional findings that could be added to the core lists as an effort in expanding the existing databases. Finally, findings regarding the role of ethnicity endeavours to provide a better understanding on the possibilities of miscommunication caused by the English spoken by the different ethnic groups.